Self-Concept in Childhood: The Role of Body Image and Sport Practice - Mendo-Lázaro, Santiago; Polo-del-Río, María I.; Amado-Alonso, Diana; Iglesias-Gallego, Damián; León-del-Barco, Benito (Frontiers in Psychology, 2017)
The purpose of this study was to explore the differences in satisfaction with body image depending on whether the subject practices organized sport or not, as well as the gender of the children. In addition, the study aims to examine the role of body image and the practice of organized sport on the process of building the academic, social, emotional, family and physical dimensions of self-concept in childhood. To do so, a sample of 944 pupils was used. These children were attending primary school in different centers of the Autonomous Community of Extremadura (Spain) and were between 9 and 12 years of age. The main results of the study show that three out of every four children participating in this study were not satisfied with their figure and one out of every five was very dissatisfied. The satisfaction or dissatisfaction with the figure was similar in boys and girls, although it could be appreciated that the ideal body image is partly conditioned by gender stereotypes. The children most satisfied with their body image had a greater academic and physical self-concept. The children that practiced organized sports had a greater physical and emotional self-concept. The children most dissatisfied with their body image and practiced organized sports had a lower family self-concept. All these findings are discussed with reference to previous research literature.